Monitoring miRNA Expression and Activity in Mammalian Oocytes and Early Embryos - Kataruka, Shubhangini; Svoboda, Petr (Methods in molecular biology (Clifton, N.J.), 2025)
MicroRNAs (miRNAs), genome-encoded small RNAs associated with Argonaute proteins, are important negative regulators of gene expression in mammalian cells. miRNAs usually partially base pair with mRNAs, suppress their translation, and destabilize them. Sufficient miRNA abundance is an important factor for efficient target repression. Experimental evidence suggests that oocyte growth causes a dilution effect, which reduces concentrations of maternal miRNAs and renders them functionally inefficient. Consequently, efficient target repression is retained only by those maternal miRNAs which achieve a favorable miRNA:mRNA stoichiometry. Here, we provide protocols for PCR-based quantification of miRNAs and luciferase reporter-based analysis of their activity in mammalian oocytes and early embryos.
Keywords: NanoLuc; mikro RNA; oocyty; Polymerase Chain Reaction; Mice; zvířata; Genes, Reporter; Gene Expression Regulation, Developmental; Oocytes; Zygote; miRNAs; vývojová regulace genové exprese; polymerázová řetězová reakce; Microinjection; mRNA reporter; myši; ženské pohlaví; reportérové geny; MicroRNAs; Animals; Oocyte; embryo savčí; Embryo, Mammalian; Female